Cryo-EM Structure and Activator Screening of Human Tryptophan Hydroxylase 2 - Zhu, Kongfu; Liu, Chao; Gao, Yuanzhu; Lu, Jianping; Wang, Daping; Zhang, Huawei (Frontiers in Pharmacology, 2022)
Human tryptophan hydroxylase 2 (TPH2) is the rate-limiting enzyme in the synthesis of serotonin. Its dysfunction has been implicated in various psychiatric disorders like depression, autism and bipolar disorder. TPH2 is typically decreased in stability and catalytic activity in patients, thus screening of molecules capable of binding and stabilizing the structure of TPH2 in activated conformation is desired for the drug development in mental disorders treatment. Here, we solved the 3.0 Å cryo-EM structure of TPH2 tetramer. Based on the structure, we then conducted allosteric sites prediction and small molecule activator screening to the obtained cavity. ZINC000068568685 was successfully selected as the best candidate with highest binding affinity. To better understand the driving forces and binding stability of the complex, we performed MD simulation which indicates that ZINC000068568685 has great potential to stabilize the folding of TPH2 tetramer to facilitate its activity. The research might shed light on the development of novel drugs targeting TPH2 for the treatment of psychological disorders.